Angular momentum density of a circularly polarized paraxial optical vortex - Victor Kotlyar; Alexey Kovalev (Компьютерная оптика, 2018)
We obtain general analytic expressions for the angular momentum density of a vectorial circularly polarized paraxial optical vortex. It is shown that for any vortex field with the rotational symmetry and circular polarization, an effect of the “angular tractor” takes place, which means that the flow of light energy rotates around the optical axis clockwise or counter-clockwise at different radii in the beam cross section. It is also shown that on the circles of these radii in the beam cross section, the axial component of the angular momentum density of the vortex light field changes its sign. Thus, microparticles trapped in the vortex beam at different radii will rotate either clockwise or counterclockwise.